Karakteristik Pasien Lesi Prakanker Serviks di Rumah Sakit Tersier Jawa Barat, Indonesia - Maulana, Akbar; Dewayani, Birgitta Maria; Hernowo, Bethy Surjawathy (Majalah Patologi Indonesia, 2022)
BackgroundThe incidence of cervical cancer was continues to increase even though various risk factors and prevention efforts have been made.Cervical cancer begins with the development of a precancerous lesion (Cervical Intraepithelial Neoplasia/CIN) which is an abnormalcell growth in the cervical epithelium. This study aims to see the proportion of risk factors for cervical cancer in CIN patients at Dr.Hasan Sadikin, Bandung.MethodsThis study used a cross-sectional retrospective descriptive research method using secondary data of CIN patients for the periodJanuary 2016 - December 2020 from the archives of the anatomical pathology laboratory and clinical medical records of patients inthe form of age, marriage history, total parity, age at marriage, age at menarche, usage of hormonal contraceptives, smoking habits,clinical symptoms and histopathological degrees.ResultThere were total sample 40 cases of CIN. The 41-50 year age category is the largest age range of all NIS cases (35%). The resultsof this research data were history of marriage 1x (85%), age at marriage in the range of 20-30 years (47.5%), history of menarche inthe age range 10-15 years (90%), history of multiparous (65%), used of hormonal contraceptives (52.5%), non-smoking habits(67.5%), clinical symptoms of vaginal bleeding (42.5%) and histopathological grade of CIN 1 (47.5%).ConclusionCervical precancerous lesions at RSUP Dr. Hasan Sadikin occurred between fourth and fifth decades of life with a history of beingmarried once, multiparous, married at the age of 20-30 years, menarche at the age of 10-15 years, using hormonal contraception,not smoking, complaints of vaginal bleeding and the majority of cases were CIN 1.